Tonic and burst spinal cord stimulation waveforms for the treatment of chronic, intractable pain: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Slavin, Konstantin; North, Richard; Deer, Timothy; Staats, Peter; Davis, Kristina; Diaz, Roni
Abstract Background Burst stimulation is a novel form of neurostimulation for the treatment of chronic pain which has demonstrated promise in small uncontrolled studies, but has not yet gained approval for use in the U.S. We report the study methods for an ongoing multicenter, randomized, controlled, cross-over study designed to gain United States Food and Drug Administration (FDA) approval for burst stimulation. Methods Participants who are candidates for a currently approved neurostimulation device were enrolled and screened. Participants who fail a tonic trial evaluation, have significant depressive symptoms, or evidence lack of compliance with study procedures by failing to complete 7 days of a Pain Diary are excluded. Participants receiving a permanent implant are randomized to receive: (1) 12 weeks of tonic followed by 12 weeks of burst stimulation or (2) 12 weeks of burst stimulation followed by 12 weeks of tonic stimulation. Assessments occur at 6, 12, 18, and 24 weeks. After 24 weeks, participants choose their preferred therapy and are assessed every 6 months for up to 2 years. All patients had the device leads inserted at the site of a successful tonic stimulation trial. Assessments include: a Pain Diary using a Visual Analog Scale (VAS) for overall, trunk, and limb pain, the Beck Depression Inventory, the Pain Catastrophizing Scale, the Oswestry Disability Index, paresthesia, satisfaction, and therapy preference. Reported adverse events are collected throughout the study. The primary endpoint is the noninferiority of burst stimulation compared to tonic measured by the within-subject difference in the mean overall VAS score at the end of each 12-week stimulation period. Discussion This trial represents the largest controlled trial of burst stimulation to date, and is expected to yield important information regarding the safety and efficacy of burst stimulation. Trial registration ClinicalTrials.gov, NCT02011893 . Registered on 10 December 2013.